Acanthocephalans parasites of two Characiformes fishes as bioindicators of cadmium contamination in two neotropical rivers in Brazil - Duarte, Gisele Silva Costa; Lehun, Atsler Luana; Leite, Lucas Aparecido Rosa [UNESP]; Consolin-Filho, Nelson; Bellay, Sybelle; Takemoto, Ricardo Massato (Elsevier, 2020)
Studies have demonstrated the role of acanthocephalan as environmental bioindicators. The dynamics in the parasite-host relationship that define the patterns of distribution of trace metals in parasites and, in its host, are extremely variable. In addition, the neotropical region, which is a major maintainer of the biodiversity of fish and parasites, remains little explored in this subject. Therefore, our objective was to analyze and compare the concentration of Cadmium (Cd) in the tissues of Prochilodus lineatus and Serrasalmus marginatus collected from Baía and Paraná rivers, as well as to assess the use of acanthocephalan as environmental bioindicators of pollution and their Cd bioaccumulation capacity. We collected 53 fish, 20 specimens of Prochilodus lineatus from Paraná River and 17 from Baía River, in addition to 16 specimens of Serrasalmus marginatus from Baía River, in September 2017 and March 2018. Tissues of the fish along with their parasites were subjected a Cd concentration analysis by Atomic Absorption Spectroscopy. The results revealed that the parasites had higher concentrations than all the tissues of S. marginatus, P. lineatus from Baía River and Paraná River. The high Cd concentrations in these parasites derived from their bioaccumulation capacity, because of the absorption of nutrients directly from the intestinal content of the fish through the tegument, as well as for the presence of Cd on the surface waters of Praná River floodplain. Besides that, the Coefficient of Spearman Rank Correlation showed that the infrapopulation size seems to affect Cd bioaccumulation in the parasites, smaller infrapopulations demonstrate a higher accumulation capacity compared to the larger ones. With that, we concluded that the two acanthocephalans species analyzed in this study have a good capacity for Cd accumulation, and can be used as accumulation indicators of trace-metal pollution. Accumulation indicators provide important information on the biological availability of pollutants.
Keywords: Bioconcentration; Bioindicators; Fish; Trace element